Absence of a significant pharmacokinetic interaction between atorvastatin and fenofibrate: a randomized, crossover, study of a fixed-dose formulation in healthy Mexican subjects - Patiño-Rodríguez, Omar; Martínez-Medina, Rosa María; Torres-Roque, Irma; Martínez-Delgado, Maricela; Mares-García, América Susana; Escobedo-Moratilla, Abraham; Covarrubias-Pinedo, Amador; Arzola-Paniagua, Angélica; Herrera-Torres, José Luis; Pérez-Urizar, José (Frontiers in Pharmacology, 2015)
Several clinical trials have substantiated the efficacy of the co-administration of statins like atorvastatin and fibrates. Without information currently available about the interaction between the two drugs, a pharmacokinetic study was conducted to investigate the effect when both drugs were co-administered. The purpose of this study was to investigate the pharmacokinetic profile of tablets containing atorvastatin 20 mg, or the combination of atorvastatin 20 mg with fenofibrate 160 mg administered to healthy Mexican volunteers. This was a randomized, two-period, two-sequence, crossover study; 36 eligible subjects aged between 20 to 50 years were included. Blood samples were collected up to 96 h after dosing, and pharmacokinetic parameters were obtained by non-compartmental analysis. Adverse events were evaluated based on subject interviews and physical examinations. Area under the concentration-time curve (AUC) and maximum plasma drug concentration (Cmax) were measured for atorvastatin as the reference and atorvastatin and fenofibrate as the test product for bioequivalence design. The estimation computed (90% confidence intervals) for atorvastatin and fenofibrate combination versus atorvastatin for Cmax, AUC0-t and AUC0-∞, were 102,09, 125,95 and 120,97% respectively. These results suggest that atorvastatin and fenofibrate have no relevant clinical-pharmacokinetic drug interaction.